COMPARING WARDROBE MANUFACTURING LAYOUT IMPROVEMENT USING RANK ORDER CLUSTERING AND CORELAP ALGORITHM - Suripto Suripto; Taufik Roni Sahroni (Sean Institute, 2023)
This paper investigates the job shop layout of the manufacturing process with simulation using ARENA. A case study of panel components, the manufacturer of modular cabinet was used. The purpose of this paper is to speed up production effectively by control materials handling and reduce preparation time. Data and specifications of cabinet and wood machinery’s coordinate were collected. Group technology (GT) based on ROC (rank order clustering) method and Corelap algorithm were used to redesign the improvement layout. Simulation the new layout using ARENA software. The result show that after using GT and ROC method to create new improvement layout, can reduce the distance of material handling by 126.9 m (30.86%). Therefore, ROC was chosen for implementation of actual future production process. Arena simulation allows manufacturer to implement with various scenario without interfering with the existing process.